Alih Wahana Cerita Rakyat Legenda Malin Kundang ke Film Animasi - Piliang, Wilda Srihastuty Handayani; Andriyani, Noni (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
The digitization of folklore will have a lot of impact, either on folklore itself or even greater on the folklore culture from which it originates. Folktale are the most digitized folklore. Folktale are turned into animated films on social media. As a product of culture, folktale contain local wisdom and values. This is the urgency of this research, whether there are additions, reductions, or varied changes from folktale that are already in written form to the form of animated films on social media like YouTube. Then, how do these additions, reductions, or varied changes affect the existence of the folktale? The theories used are transformation and ecranization. This research is qualitative, with description methods and content analysis techniques. The research data sources are the folktale Legend of Malin Kundang in the book Collection of Indonesian Folk Stories published by Dua Media and the animated film